(untitled) (Vietnam Journal of Community Medicine, 2021)
Introduction: In Vietnam, using a muscle accelerator to measure the TOF index to monitor residue neuromuscular blockade has not been performed routinely, extubation is mainly based on subjective clinical assessments. Methods: A cross-sectional study on 96 patients undergoing laparoscopic appendectomy at Nguyen Tri Phuong Hospital, from November 2020 to May 2021. Objectives: The study was conducted with 2 objectives including (1) Determine the progression of TOF index at 7 time points: immediately after arriving in the recovery room, after extubation, 15 minutes, 30 minutes, 60 minutes, 90 minutes, 120 minutes after extubation; (2) Determination of residual muscle relaxant rate of patients undergoing laparoscopic appendectomy at Nguyen Tri Phuong Hospital. Results: The average TOF ≥ 0,9 index after laparoscopic appendectomy at the time of resuscitation was 88.11%, extubation was 90.53% and at 120 minutes after extubation. is 99.88%. Residual muscle relaxation after surgery when TOF index < 0.9. At the time of resuscitation, the highest residual rate of muscle relaxant accounted for 58.33%, followed by the time of extubation 39.58%, 15 minutes after extubation was 21.88%. Until 120 after extubation, there is no case that has residue neuromuscular blockade. Conclusion: Through the study results, it is necessary to monitor patients undergoing laparoscopic appendectomy with quantitative devices to more accurately assess the clinical index of muscle relaxation.